Bandwidth enhancement of compact monopole antenna with triple band rejections. Issue 1 (1st January 2016) - Li, Tong; Zhu, Cheng; Cao, Xiangyu; Gao, Jun
Abstract : A compact monopole antenna with enhanced bandwidth and triple band rejections for ultra‐wideband applications is presented. The base of the proposed antenna is a semicircular patch which is fed by a modified tapered coplanar waveguide line. By using the trident‐shaped feed line, much wider impedance bandwidth is obtained. To avoid potential interferences, two trapezoid stubs and a C‐shaped stub are printed on the back surface of the substrate and are connected to the antenna through three vias. The proposed antenna is practically fabricated with a compact size of 20 × 24 mm 2 . Good agreement is achieved between the simulation and measurement, which shows that the proposed antenna offers a very wide bandwidth from 3.02 to 20.8 GHz (149%) with triple band rejections covering the 3.5 GHz WiMAX and 5.2/5.8 GHz WLAN bands.